2009
DOI: 10.1161/circulationaha.108.771401
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Substrate Mapping in Brugada Syndrome

Abstract: Marked regional endocardial conduction delay and heterogeneities in repolarization exist in BS. Wave break in areas of maximal conduction delay appears to be critical in the initiation and maintenance of ventricular tachycardia. These data indicate that further studies of mapping BS to identify slow-conduction zones should be considered to determine their role in spontaneous ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Together, these two properties provide conditions for sustained reentrant excitation. Their coexistence in the substrate of BrS patients has been suggested by other recent studies; 2728 it is consistent with the high incidence of arrhythmic SCD. Interestingly, most arrhythmic events occur during bradycardia.…”
Section: Discussionsupporting
confidence: 86%
“…Together, these two properties provide conditions for sustained reentrant excitation. Their coexistence in the substrate of BrS patients has been suggested by other recent studies; 2728 it is consistent with the high incidence of arrhythmic SCD. Interestingly, most arrhythmic events occur during bradycardia.…”
Section: Discussionsupporting
confidence: 86%
“…Noncontact mapping of the RV demonstrated moderately prolonged total RV endocardial activation time of 82 ms in sinus rhythm versus <65 ms recorded in healthy controls 20 . Furthermore, the maximum endocardial activation gradient was only 0.22 mm/ms, which is 40% of that recorded in healthy controls by our group using this technique (0.51 ± 0.15 mm/ms) 21 . Fractionated and low-amplitude electrograms also were identified in the posterior RV wall and posterolateral RV outflow tract segments (Figure 1).…”
Section: Resultsmentioning
confidence: 40%
“…119 The investigators identified marked regional endocardial conduction delay and heterogeneities in repolarisation in patients with BrS and proposed that the slow-conduction zones may have a role in the initiation and maintenance of ventricular arrhythmias.…”
Section: Inherited Arrhythmogenic Diseasesmentioning
confidence: 99%